10.1016/s1541-9800(07)70091-1 (CrossRef Listing of Deleted DOIs, 2000)
How might public sentiment respond to information that incarceration may not always achieve one of its core goals of deterring crime or that it could even, perversely, increase reoffending? Across three experiments, participants provided prison sentence length recommendations for a violent or nonviolent criminal case vignette. Before doing so, they were randomized to view either criminogenic evidence (incarceration increases reoffending), deterrent evidence (incarceration decreases reoffending), "no-effect" evidence (incarceration has no effect on reoffending), or no evidence at all. We predicted and found that participants exposed to criminogenic evidence recommended significantly shorter (up to one-third shorter) prison sentences than those exposed to deterrent evidence. Our predictions regarding the "no-effect" and "no evidence" conditions were partially supported. This pattern of results demonstrates clear public support for reducing criminogenic consequences of incarceration, but this support may be qualified by other competing punishment motivations. These findings suggest how information campaigns could play a role in altering public sentiment toward criminal justice policies.